A Driverless Alternative: Fleet Size and Cost Requirements for a Statewide Autonomous Taxi Network in New Jersey. Issue 1 (January 2014) - Brownell, Chris; Kornhauser, Alain
Over the past six decades, as private automobiles have become more affordable and more universal among American families, previously uncounted costs for cars have come to the forefront of the modern transportation debate, with some activists calling for an end to cars. This paper identifies five transit criteria that a transportation system must satisfy if it hopes to dethrone the individually owned and operated car as king of the road: (a) a solution to the congestion problem, (b) safety improvements over conventional manually operated cars, (c) lesser impact on the environment, (d) economic feasibility, and (e) comfort and convenience to rival the automobile. Given recent advancements in the field of vehicle autonomy, a potential solution to the car's growing problems has presented itself: an autonomous taxi network (ATN). Drawing from the classic personal rapid transit model as well as Mark Gorton's idea of smart paratransit, two potential designs for an ATN are presented and compared with one another, and the viability of the ATN concept is explored in view of statewide transportation demand in New Jersey. With travel demand as generated by Talal Mufti in 2012, the smart paratransit model emerges as the more economically viable implementation, requiring a fleet size between 1.6 and 2.8 million six-passenger vehicles to meet the state's travel demand in its entirety, at a cost to consumers of $16.30 to $23.50 per person per day.